Sharp drop in under-five mortality and associated factors in Burkina Faso from 2010 to 2021: is it a composition or performance effect? - Bassinga, Hervé; Ouedraogo, Sibiri Clément; Bado, Aristide Romaric; Bazié, Herman; Kouadima Diallo, Kadidia; Savadogo, Yacouba (Frontiers in Public Health, 2025)
BackgroundLong maintained above 100 ‰ since the 1960s, under-five mortality rates in Burkina Faso have experienced a significant decline, although the specific sources of change remain difficult to identify. Notably, under-five mortality increased from 187 ‰ in 1993 to 219 ‰ in 1998. Subsequently, a steady decrease was observed, with rates falling to 184 ‰ in 2003, 129 ‰ in 2010, and ultimately reaching 48 ‰ in 2021.ObjectivesThe aim of this study was to analyze the sources of change and the factors that have contributed to the decline in under-five mortality rates in Burkina Faso from 2010 to 2021.MethodUtilizing data from Demographic and Health Surveys (DHS), this analysis encompassed the period from 2010 to 2021 and used an Oaxaca-Blinder multivariate decomposition method. This approach facilitated the differentiation of the components of change that can be attributed to the demographic composition (structure) of the population versus those attributable to behavioral changes and policy effectiveness. The analysis samples consisted of 15,045 and 12,242 children in 2010 and 2021, respectively.ResultsThe results showed that the observed decline in under-five mortality was largely attributable to changes in unobserved variables rather than to changes in population structure. Specifically, changes in population structure accounted for only 23% of the decline in under-five mortality between 2010 and 2021, while the effect of overall variation in coefficients related to the efficacy of control measures and behavioral changes accounted for 77% of the decline. Among the factors associated with performance and behavioral changes, the involvement of unemployed women (13.1%) has significantly contributed to the reduction of child mortality rates.ConclusionUrbanization has led to a decline in under-five mortality rates, likely attributable to improved access to health services. Therefore, regions such as the Sahel and the Southwest, which have high mortality rates, should be prioritized for targeted intervention. It is imperative to enhance healthcare provision in rural areas to mitigate disparities. To maximize the efficacy of these interventions, a holistic approach that encompasses advancements in education, economic development, and sanitation is essential. In conjunction with development efforts, behavior change communication constitutes a critical lever in the fight against child mortality.